Lightweight foamed aluminum-based integrated structural member for electronic equipment case
By using modified foaming agents and binders, combined with biomimetic ventilation channels and surface conductive layer design, the problems of foaming agent adsorption of water vapor and insufficient bonding force of binders are solved, thereby improving the compressive strength and structural stability of electronic equipment chassis.
Patent Information
- Application Number
- CN202511507192.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2026-01-16
AI Technical Summary
Existing electronic device enclosures have foaming agents that easily absorb moisture, leading to reduced gas production efficiency. The adhesives have insufficient bonding strength, resulting in low flexural strength. Furthermore, epoxy resins exhibit poor structural stability at high temperatures.
Modified foaming agents and modified binders are used, and epoxy resin is modified with tetraethyl orthosilicate and silane coupling agent KH-560 to form a silica coating layer and chemical bond, which enhances the interfacial bonding force. This is combined with the design of biomimetic ventilation channels and surface conductive layers.
It improves the density and mechanical properties of gradient aluminum foam matrix, enhances compressive strength and structural stability, and adapts to the high-temperature environment of electronic equipment.
Smart Images

Figure CN121339445A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic device protective structure technology, specifically to a lightweight foam-based integrated structural component for electronic device chassis. Background Technology
[0002] With the rapid development of electronic technology, electronic devices are evolving towards miniaturization and high performance. As the carrier of the device, the electronic device chassis must not only provide mechanical support and protection for the internal components, but also deal with issues such as heat dissipation and electromagnetic interference.
[0003] In existing technologies, titanium hydride is used as the foaming agent. It easily adsorbs water vapor in the air and hydrolyzes during storage or processing, which reduces the actual gas production efficiency. In addition, the hydrogen produced by hydrolysis may cause pore defects in the matrix. Traditional binders and aluminum powder are only physically adsorbed and bonded together. There are gaps at the interface, which makes them prone to delamination under external force, resulting in low bending strength. At the same time, epoxy resin is prone to softening when the temperature inside the electronic device chassis is high, which reduces the stability of the matrix structure.
[0004] Based on this, the present invention provides a lightweight foam-based integrated structural component for electronic device chassis. Summary of the Invention
[0005] The purpose of this invention is to provide a lightweight integrated aluminum foam matrix structure for electronic device chassis. The integrated aluminum foam matrix structure of this invention not only has a low gradient aluminum foam matrix density and low resistivity of the surface conductive layer, but also has high compressive strength of the gradient aluminum foam matrix.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a lightweight foamed aluminum-based integrated structural component for electronic device chassis, comprising a gradient foamed aluminum matrix, a biomimetic ventilation channel, and a surface conductive layer; The raw materials for the gradient aluminum foam matrix include aluminum powder, modified foaming agent, reinforcing phase, modified binder and dispersant; The biomimetic ventilation channel includes preliminary processing, cutoff waveguide structure processing, and micron-level fin processing; The raw materials for the surface conductive layer include nickel sulfate, a modified reducing agent, a complexing agent, a buffer, and a stabilizer.
[0007] Preferably, the modified foaming agent in the gradient aluminum foam matrix raw material is titanium hydrogenated with tetraethyl orthosilicate, the reinforcing phase is nano-silicon carbide particles, the modified binder is epoxy resin modified with silane coupling agent KH-560, and the dispersant is octadecanoic acid.
[0008] Preferably, the preparation steps of the modified foaming agent are as follows: take titanium hydride powder with a particle size of 10-20 μm, disperse it in a 3:1 volume ratio ethanol-water mixed solution, and sonicate for 30 min to form a suspension; add 5-8% of tetraethyl orthosilicate by mass of titanium hydride, add dilute ammonia dropwise to adjust the pH to 8-9, stir at 30°C for 2 h, so that tetraethyl orthosilicate hydrolyzes on the surface of titanium hydride to generate silica sol; filter and vacuum dry at 80°C for 4 h to obtain silica-coated titanium hydride, thus obtaining the modified foaming agent.
[0009] Preferably, the preparation steps of the modified adhesive are as follows: placing epoxy resin in a three-necked flask, heating it to 60-70°C in a water bath with a stirring speed of 300-500 r / min, slowly adding silane coupling agent KH-560 dropwise at 3-5% of the mass of epoxy resin, stirring at a stirring speed of 300-500 r / min for 1-1.5 h, and cooling to room temperature to obtain modified epoxy resin, thus obtaining the modified adhesive.
[0010] Preferably, the gradient aluminum foam matrix is composed of the following raw materials in parts by weight: 100 parts aluminum powder, 1-3 parts modified foaming agent, 5-8 parts reinforcing phase, 5-10 parts modified binder, and 0.5-1 parts dispersant.
[0011] Preferably, the preparation steps of the gradient aluminum foam matrix are as follows: Step 1: Weigh aluminum powder, modified foaming agent, reinforcing phase, and dispersant according to the mass ratio, add them to a mixer, and mix at 300-500 r / min for 20-30 min under inert gas protection to obtain premixed powder; Step 2: Add the modified binder to the premixed powder and continue mixing at 200-300 r / min for 15-20 min to obtain the molding powder. Step 3: Load the molding powder into the mold and cold press it under a pressure of 15-20MPa for 5-10 minutes to obtain the green body; Step 4: Place the green billet into a sintering furnace, first heat it to 450℃ at 5℃ / min and hold it for 0.5h; then heat it to 620-650℃ at 3℃ / min and hold it for 2-3h for foaming and sintering; finally cool it to room temperature with the furnace to obtain a gradient aluminum foam matrix.
[0012] Preferably, the complexing agent is sodium citrate, the buffer is sodium acetate, and the stabilizer is thiourea.
[0013] Preferably, the modified reducing agent is... A simple compound of doped sodium hypophosphite and hydrazine hydrate in a mass ratio of (3-5):1 is added directly to the plating solution during use.
[0014] Preferably, the preparation steps of the surface conductive layer are as follows: Step 1, Matrix pretreatment: Immerse the gradient aluminum foam matrix in sodium hydroxide solution for degreasing, then immerse it in nitric acid solution for acid washing and activation, pre-immerse it in an aqueous solution containing 2% complexing agent, soak it at 30℃ for 3 minutes, rinse it with deionized water and drain it. Step 2, Plating solution preparation: The chemical plating solution is composed of the following raw materials in parts by weight: 100 parts nickel sulfate, 8-12 parts modified reducing agent, 5-10 parts complexing agent, 3-6 parts buffer, and 1-2 parts stabilizer. First, dissolve the nickel sulfate, complexing agent, and buffer in deionized water and stir until completely dissolved. Then adjust the pH to 4.5-5.5. Next, add the modified reducing agent and stabilizer, stir evenly, and heat to 50-55℃ to obtain the chemical plating solution. Step 3, chemical plating: Suspend the pretreated gradient aluminum foam substrate in the chemical plating solution, maintain the solution temperature at 50-55℃ and the stirring speed at 200r / min, and plating for 30-40min; Step 4, Post-treatment: Take out the plated substrate, rinse it three times with 60℃ deionized water, and dry it in an 80℃ forced-air drying oven for 20 minutes; then put it into a vacuum furnace and heat it to 150℃, keep it at that temperature for 1 hour, and then cool it to room temperature with the furnace to complete the preparation of the surface conductive layer.
[0015] Preferably, the preparation steps of the biomimetic ventilation channel are as follows: Step 1, Preliminary processing: The gradient aluminum foam matrix is pre-formed using CNC milling technology. The milling speed is 8000-10000 r / min, the feed rate is 500-800 mm / min, and the channel cross-section is rectangular with a width of 5-10 mm and a height of 3-5 mm. Step 2, Cut-off waveguide structure processing: On the inner wall of the channel after preliminary processing, the cut-off waveguide structure is processed by laser engraving. The side length of the cross section of the waveguide structure is 2-5mm, and the spacing between adjacent waveguides is 3-6mm. Step 3, Micron-level fin processing: Micron-level fins are processed on the surface of the waveguide structure using electrolytic etching. The fin height is 0.5-1mm, the fin spacing is 1-2mm, the etching current density is 10-15A / dm², and the etching time is 10-15min to obtain a biomimetic ventilation channel.
[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, titanium hydride, after being modified with tetraethyl orthosilicate, forms a silica coating layer on its surface. This layer isolates the titanium hydride from contact with external moisture, preventing hydrolysis and reducing moisture absorption while ensuring stability during storage and processing. Furthermore, the silica increases the initial decomposition temperature of the titanium hydride, better matching its sintering temperature with aluminum. The increased peak gas generation temperature and prolonged gas generation time prevent pore collapse caused by concentrated gas generation. The siloxane groups of the coating layer form chemical bonds with the hydroxyl groups on the surface of the reinforcing phase and the siloxane groups of the modified binder, which enhances the interfacial bonding, reduces the agglomeration rate of titanium hydride in aluminum powder, improves the compatibility with aluminum powder and binder, and synergistically improves the density and mechanical properties of the gradient foam aluminum matrix.
[0017] 2. In this invention, after the epoxy resin is modified with the silane coupling agent KH-560, the epoxy groups in the molecule form a chemical bond with the epoxy resin, and the silane groups can form -Si-O- covalent bonds with the hydroxyl groups on the surface of the reinforcing phase, thereby improving the interfacial bonding force and solving the delamination problem caused by ordinary adhesives relying solely on physical adsorption. At the same time, the glass transition temperature is increased, allowing it to maintain stable mechanical properties at a high temperature of 100°C, making it suitable for the working environment of electronic devices. The compatibility with aluminum powder and modified foaming agent is enhanced, and the interaction of the silane groups promotes uniform dispersion of raw materials, inhibits agglomeration of the reinforcing phase, and synergistically improves the flexural strength and structural stability of the gradient foam aluminum matrix. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] It should be noted that all raw materials used in the following experiments are commercially available.
[0020] Example 1: A lightweight integrated foamed aluminum matrix structural component for electronic device chassis, comprising a gradient foamed aluminum matrix, a biomimetic ventilation channel, and a surface conductive layer; The raw materials for gradient aluminum foam matrix include aluminum powder, modified foaming agent, reinforcing phase, modified binder and dispersant; The biomimetic ventilation channel includes preliminary processing, cutoff waveguide structure processing, and micron-level fin processing; The raw materials for the surface conductive layer include nickel sulfate, modified reducing agent, complexing agent, buffer, and stabilizer.
[0021] The modified foaming agent in the gradient aluminum foam matrix is titanium hydrogenated with tetraethyl orthosilicate, the reinforcing phase is nano-silicon carbide particles, the modified binder is epoxy resin modified with silane coupling agent KH-560, and the dispersant is octadecanoic acid.
[0022] The preparation steps of the modified foaming agent are as follows: Take titanium hydride powder with a particle size of 10 μm, disperse it in a 3:1 volume ratio ethanol-water mixed solution, and sonicate for 30 min to form a suspension; add 5% of the mass of titanium hydride with tetraethyl orthosilicate, add dilute ammonia dropwise to adjust the pH to 8, stir at 30℃ for 2 h to hydrolyze tetraethyl orthosilicate on the surface of titanium hydride to generate silica sol; filter and vacuum dry at 80℃ for 4 h to obtain silica-coated titanium hydride, thus obtaining the modified foaming agent.
[0023] The preparation steps of the modified adhesive are as follows: place epoxy resin in a three-necked flask, heat it to 60°C in a water bath with a stirring speed of 300 r / min, slowly add silane coupling agent KH-560 dropwise at 3% of the mass of epoxy resin, stir at a stirring speed of 300 r / min for 1 h, and cool to room temperature to obtain modified epoxy resin and modified adhesive.
[0024] The gradient aluminum foam matrix is composed of the following raw materials in parts by weight: 100 parts aluminum powder, 1 part modified foaming agent, 5 parts reinforcing phase, 5 parts modified binder, and 0.5 parts dispersant.
[0025] The preparation steps of gradient aluminum foam matrix are as follows: Step 1: Weigh aluminum powder, modified foaming agent, reinforcing phase, and dispersant according to the mass ratio, add them to a mixer, and mix at 300 r / min for 20 min under inert gas protection to obtain premixed powder; Step 2: Add the modified binder to the premixed powder and continue mixing at 200 r / min for 15 min to obtain the molding powder. Step 3: Load the molding powder into the mold and cold press it under a pressure of 15MPa for 5 minutes to obtain the green body; Step 4: Place the green billet into the sintering furnace, first heat it to 450℃ at 5℃ / min and hold it for 0.5h; then heat it to 620℃ at 3℃ / min and hold it for 2h for foaming and sintering; finally cool it to room temperature with the furnace to obtain the gradient aluminum foam matrix.
[0026] The complexing agent in the surface conductive layer material is sodium citrate, the buffer is sodium acetate, and the stabilizer is thiourea.
[0027] The modified reducing agent is The compound of doped sodium hypophosphite and hydrazine hydrate in a mass ratio of 3:1 is added directly to the plating solution during use.
[0028] The steps for preparing the surface conductive layer are as follows: Step 1, Matrix pretreatment: Immerse the gradient aluminum foam matrix in sodium hydroxide solution for degreasing, then immerse it in nitric acid solution for acid washing and activation, pre-immerse it in an aqueous solution containing 2% complexing agent, soak it at 30℃ for 3 minutes, rinse it with deionized water and drain it. Step 2, Plating solution preparation: The chemical plating solution is composed of the following raw materials in parts by weight: 100 parts nickel sulfate, 8 parts modified reducing agent, 5 parts complexing agent, 3 parts buffer, and 1 part stabilizer. First, dissolve the nickel sulfate, complexing agent, and buffer in deionized water and stir until completely dissolved. Then adjust the pH to 4.5. Next, add the modified reducing agent and stabilizer, stir evenly, and heat to 50°C to obtain the chemical plating solution. Step 3, chemical plating: Suspend the pretreated gradient aluminum foam substrate in the chemical plating solution, maintain the solution temperature at 50℃ and the stirring speed at 200r / min, and plating for 30min; Step 4, Post-treatment: Take out the plated substrate, rinse it three times with 60℃ deionized water, and dry it in an 80℃ forced-air drying oven for 20 minutes; then put it into a vacuum furnace and heat it to 150℃, keep it at that temperature for 1 hour, and then cool it to room temperature with the furnace to complete the preparation of the surface conductive layer.
[0029] The fabrication steps of the biomimetic ventilation channel are as follows: Step 1, Preliminary processing: The gradient aluminum foam matrix is pre-formed using CNC milling technology. The milling speed is 8000 r / min, the feed rate is 500 mm / min, and the channel cross-section is rectangular with a width of 5 mm and a height of 3 mm. Step 2, Cut-off waveguide structure processing: On the inner wall of the channel after preliminary processing, the cut-off waveguide structure is processed by laser engraving. The side length of the cross section of the waveguide structure is 2mm and the spacing between adjacent waveguides is 3mm. Step 3, Micron-level fin processing: Micron-level fins are processed on the surface of the waveguide structure using electrolytic etching. The fin height is 0.5 mm, the fin spacing is 1 mm, the etching current density is 10 A / dm², and the etching time is 10 min to obtain a biomimetic ventilation channel.
[0030] Example 2: A lightweight integrated foamed aluminum matrix structural component for electronic device chassis, comprising a gradient foamed aluminum matrix, a biomimetic ventilation channel, and a surface conductive layer; The raw materials for gradient aluminum foam matrix include aluminum powder, modified foaming agent, reinforcing phase, modified binder and dispersant; The biomimetic ventilation channel includes preliminary processing, cutoff waveguide structure processing, and micron-level fin processing; The raw materials for the surface conductive layer include nickel sulfate, modified reducing agent, complexing agent, buffer, and stabilizer.
[0031] The modified foaming agent in the gradient aluminum foam matrix is titanium hydrogenated with tetraethyl orthosilicate, the reinforcing phase is nano-silicon carbide particles, the modified binder is epoxy resin modified with silane coupling agent KH-560, and the dispersant is octadecanoic acid.
[0032] The preparation steps of the modified foaming agent are as follows: Take titanium hydride powder with a particle size of 15 μm, disperse it in a 3:1 volume ratio ethanol-water mixed solution, and sonicate for 30 min to form a suspension; add tetraethyl orthosilicate at 6.5% of the mass of titanium hydride, add dilute ammonia dropwise to adjust the pH to 8.5, stir at 30℃ for 2 h, so that tetraethyl orthosilicate hydrolyzes on the surface of titanium hydride to generate silica sol; after filtration, vacuum dry at 80℃ for 4 h to obtain silica-coated titanium hydride, and obtain the modified foaming agent.
[0033] The preparation steps of the modified adhesive are as follows: place epoxy resin in a three-necked flask, heat it to 65°C in a water bath with a stirring speed of 400 r / min, slowly add silane coupling agent KH-560 dropwise at 4% of the mass of epoxy resin, stir at a stirring speed of 400 r / min for 1.2 h, and cool to room temperature to obtain modified epoxy resin and modified adhesive.
[0034] The gradient aluminum foam matrix is composed of the following raw materials in parts by weight: 100 parts aluminum powder, 2 parts modified foaming agent, 6.5 parts reinforcing phase, 7.5 parts modified binder, and 0.75 parts dispersant.
[0035] The preparation steps of gradient aluminum foam matrix are as follows: Step 1: Weigh aluminum powder, modified foaming agent, reinforcing phase, and dispersant according to the mass ratio, add them to a mixer, and mix at 400 r / min for 25 min under inert gas protection to obtain premixed powder; Step 2: Add the modified binder to the premixed powder and continue mixing at 250 r / min for 17 min to obtain the molding powder. Step 3: Load the molding powder into the mold and cold press it under a pressure of 17MPa for 7 minutes to obtain the green body; Step 4: Place the green billet into a sintering furnace, first heat it to 450℃ at 5℃ / min and hold it for 0.5h; then heat it to 635℃ at 3℃ / min and hold it for 2.5h for foaming and sintering; finally cool it to room temperature with the furnace to obtain a gradient aluminum foam matrix.
[0036] The complexing agent in the surface conductive layer material is sodium citrate, the buffer is sodium acetate, and the stabilizer is thiourea.
[0037] The modified reducing agent is The compound of doped sodium hypophosphite and hydrazine hydrate in a mass ratio of 4:1 is added directly to the plating solution during use.
[0038] The steps for preparing the surface conductive layer are as follows: Step 1, Matrix pretreatment: Immerse the gradient aluminum foam matrix in sodium hydroxide solution for degreasing, then immerse it in nitric acid solution for acid washing and activation, pre-immerse it in an aqueous solution containing 2% complexing agent, soak it at 30℃ for 3 minutes, rinse it with deionized water and drain it. Step 2, Plating solution preparation: The chemical plating solution is composed of the following raw materials in parts by weight: 100 parts nickel sulfate, 10 parts modified reducing agent, 7.5 parts complexing agent, 4.5 parts buffer, and 1.5 parts stabilizer. First, dissolve the nickel sulfate, complexing agent, and buffer in deionized water and stir until completely dissolved. Then adjust the pH to 5.0. Next, add the modified reducing agent and stabilizer, stir evenly, and heat to 52°C to obtain the chemical plating solution. Step 3, chemical plating: Suspend the pretreated gradient aluminum foam substrate in the chemical plating solution, maintain the solution temperature at 52℃ and the stirring speed at 200r / min, and plating for 35min; Step 4, Post-treatment: Take out the plated substrate, rinse it three times with 60℃ deionized water, and dry it in an 80℃ forced-air drying oven for 20 minutes; then put it into a vacuum furnace and heat it to 150℃, keep it at that temperature for 1 hour, and then cool it to room temperature with the furnace to complete the preparation of the surface conductive layer.
[0039] The fabrication steps of the biomimetic ventilation channel are as follows: Step 1, Preliminary processing: The gradient aluminum foam matrix is pre-formed using CNC milling technology. The milling speed is 9000 r / min, the feed rate is 650 mm / min, and the channel cross-section is rectangular with a width of 7 mm and a height of 4 mm. Step 2, Cut-off waveguide structure processing: On the inner wall of the channel after preliminary processing, the cut-off waveguide structure is processed by laser engraving. The side length of the cross section of the waveguide structure is 3.5mm, and the spacing between adjacent waveguides is 4.5mm. Step 3, Micron-level fin processing: Micron-level fins are processed on the surface of the waveguide structure using electrolytic etching. The fin height is 0.7 mm, the fin spacing is 1.5 mm, the etching current density is 12 A / dm², and the etching time is 12 min to obtain a biomimetic ventilation channel.
[0040] Example 3: A lightweight integrated foamed aluminum matrix structural component for electronic device chassis, comprising a gradient foamed aluminum matrix, a biomimetic ventilation channel, and a surface conductive layer; The raw materials for gradient aluminum foam matrix include aluminum powder, modified foaming agent, reinforcing phase, modified binder and dispersant; The biomimetic ventilation channel includes preliminary processing, cutoff waveguide structure processing, and micron-level fin processing; The raw materials for the surface conductive layer include nickel sulfate, modified reducing agent, complexing agent, buffer, and stabilizer.
[0041] The modified foaming agent in the gradient aluminum foam matrix is titanium hydrogenated with tetraethyl orthosilicate, the reinforcing phase is nano-silicon carbide particles, the modified binder is epoxy resin modified with silane coupling agent KH-560, and the dispersant is octadecanoic acid.
[0042] The preparation steps of the modified foaming agent are as follows: Take titanium hydride powder with a particle size of 20 μm, disperse it in a 3:1 volume ratio ethanol-water mixed solution, and sonicate for 30 min to form a suspension; add tetraethyl orthosilicate at 8% of the mass of titanium hydride, add dilute ammonia dropwise to adjust the pH to 9, stir at 30℃ for 2 h to hydrolyze tetraethyl orthosilicate on the surface of titanium hydride to generate silica sol; filter and vacuum dry at 80℃ for 4 h to obtain silica-coated titanium hydride, thus obtaining the modified foaming agent.
[0043] The preparation steps of the modified adhesive are as follows: place epoxy resin in a three-necked flask, heat it to 70°C in a water bath with a stirring speed of 500 r / min, slowly add silane coupling agent KH-560 dropwise at 5% of the mass of epoxy resin, stir at a stirring speed of 500 r / min for 1.5 h, and cool to room temperature to obtain modified epoxy resin and modified adhesive.
[0044] The gradient aluminum foam matrix is composed of the following raw materials in parts by weight: 100 parts aluminum powder, 3 parts modified foaming agent, 8 parts reinforcing phase, 10 parts modified binder, and 1 part dispersant.
[0045] The preparation steps of gradient aluminum foam matrix are as follows: Step 1: Weigh aluminum powder, modified foaming agent, reinforcing phase, and dispersant according to the mass ratio, add them to the mixer, and mix at 500 r / min for 30 min under inert gas protection to obtain premixed powder; Step 2: Add the modified binder to the premixed powder and continue mixing at 300 r / min for 20 min to obtain the molding powder. Step 3: Load the molding powder into the mold and cold press it under a pressure of 20MPa for 10 minutes to obtain the green body; Step 4: Place the green billet into the sintering furnace, first heat it to 450℃ at 5℃ / min and hold it for 0.5h; then heat it to 650℃ at 3℃ / min and hold it for 3h for foaming and sintering; finally cool it to room temperature with the furnace to obtain the gradient aluminum foam matrix.
[0046] The complexing agent in the surface conductive layer material is sodium citrate, the buffer is sodium acetate, and the stabilizer is thiourea.
[0047] The modified reducing agent is The compound of doped sodium hypophosphite and hydrazine hydrate in a mass ratio of 5:1 is added directly to the plating solution during use.
[0048] The steps for preparing the surface conductive layer are as follows: Step 1, Matrix pretreatment: Immerse the gradient aluminum foam matrix in sodium hydroxide solution for degreasing, then immerse it in nitric acid solution for acid washing and activation, pre-immerse it in an aqueous solution containing 2% complexing agent, soak it at 30℃ for 3 minutes, rinse it with deionized water and drain it. Step 2, Plating solution preparation: The chemical plating solution is composed of the following raw materials in parts by weight: 100 parts nickel sulfate, 12 parts modified reducing agent, 10 parts complexing agent, 6 parts buffer, and 2 parts stabilizer. First, dissolve the nickel sulfate, complexing agent, and buffer in deionized water and stir until completely dissolved. Then adjust the pH to 5.5. Next, add the modified reducing agent and stabilizer, stir evenly, and heat to 55°C to obtain the chemical plating solution. Step 3, chemical plating: Suspend the pretreated gradient aluminum foam substrate in the chemical plating solution, maintain the solution temperature at 55℃ and the stirring speed at 200r / min, and plating for 40min; Step 4, Post-treatment: Take out the plated substrate, rinse it three times with 60℃ deionized water, and dry it in an 80℃ forced-air drying oven for 20 minutes; then put it into a vacuum furnace and heat it to 150℃, keep it at that temperature for 1 hour, and then cool it to room temperature with the furnace to complete the preparation of the surface conductive layer.
[0049] The fabrication steps of the biomimetic ventilation channel are as follows: Step 1, Preliminary machining: The gradient aluminum foam matrix is pre-formed using CNC milling technology. The milling speed is 10000 r / min, the feed rate is 800 mm / min, and the channel cross-section is rectangular with a width of 10 mm and a height of 5 mm. Step 2, Cut-off waveguide structure processing: On the inner wall of the channel after preliminary processing, the cut-off waveguide structure is processed by laser engraving. The side length of the cross section of the waveguide structure is 5mm and the spacing between adjacent waveguides is 6mm. Step 3, Micron-level fin processing: Micron-level fins are processed on the surface of the waveguide structure using electrolytic etching. The fin height is 1mm, the fin spacing is 2mm, the etching current density is 15A / dm², and the etching time is 15min to obtain a biomimetic ventilation channel.
[0050] Comparative Example 1: The difference between this comparative example and Examples 1-3 is that no modified foaming agent is used in this comparative example.
[0051] Comparative Example 2 differs from Examples 1-3 in that no modified binder is used in this comparative example.
[0052] Comparative Example 3 differs from Examples 1-3 in that no modified reducing agent is used in this comparative example.
[0053] Performance testing: Performance tests were conducted on the products prepared in Examples 1, 2, 3, Comparative Examples 1, 2, and 3. Gradient aluminum foam matrix density test: Select a representative gradient aluminum foam matrix sample and weigh its mass m using an electronic balance with an accuracy of 0.001g; use the displacement method to completely immerse the sample in a graduated cylinder containing deionized water and read the volume change of water to determine the sample volume V; calculate the density according to the density formula ρ=m / V, repeat the test 3 times and take the average value, test according to: GB / T5163-2006. Compressive strength test of gradient aluminum foam matrix: The compressive strength of gradient aluminum foam matrix was tested using an electronic universal testing machine. The specimen was processed into a uniformly sized cube and placed on the pressure platform of the testing machine, with the center of the specimen aligned with the center of the indenter. Axial compression was applied at a loading rate of 1 mm / min until failure, and the maximum load Fmax was recorded. The compressive strength was calculated based on the stress area S of the specimen using the formula σ = Fmax / S. Test standard: ASTM B524. Surface conductive layer resistivity test: The resistivity of the surface conductive layer is tested using the four-probe method. Using a four-probe tester, four probes are pressed vertically and evenly onto the flat test area of the surface conductive layer. After applying a constant current, the voltage drop between adjacent probes is measured. Then, the resistivity of the surface conductive layer is calculated by combining the resistivity calculation formula of the four-probe method. The test is repeated in 5 different areas and the average value is taken. Test standard: GB / T1551-2009.
[0054] The obtained test data are recorded in Table 1 below: Testing items Gradient foam aluminum-based density (g / cm³) Compressive strength (MPa) of graded aluminum foam matrix Surface conductive layer resistivity (μΩ·cm) Example 1 0.85 32 1.6 Example 2 0.82 35 1.5 Example 3 0.80 38 1.4 Comparative Example 1 1.10 22 2.2 Comparative Example 2 0.95 25 2.0 Comparative Example 3 0.88 30 16.8 By comparing and analyzing the relevant data in Table 1, it can be seen that the lightweight integrated aluminum foam matrix structure of this invention for electronic device chassis not only has a low gradient aluminum foam matrix density and low surface conductive layer resistivity, but also, due to the synergistic effect of the gradient structure and the nano-silicon carbide reinforcing phase, improves the mechanical properties of the aluminum foam matrix while reducing density, thus resulting in higher compressive strength of the gradient aluminum foam matrix. This indicates that the lightweight integrated aluminum foam matrix structure for electronic device chassis provided by this invention has a broader market prospect and is more suitable for widespread application.
[0055] In the description of this specification, references to terms such as "an embodiment," "example," and "specific example" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0056] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A lightweight integrated foamed aluminum-based structural component for electronic device chassis, characterized in that: Includes a gradient aluminum foam matrix, biomimetic ventilation channels, and a surface conductive layer; The raw materials for the gradient aluminum foam matrix include aluminum powder, modified foaming agent, reinforcing phase, modified binder and dispersant; The biomimetic ventilation channel includes preliminary processing, cutoff waveguide structure processing, and micron-level fin processing; The raw materials for the surface conductive layer include nickel sulfate, a modified reducing agent, a complexing agent, a buffer, and a stabilizer.
2. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that: The modified foaming agent in the gradient aluminum foam matrix raw material is titanium hydrogenated with tetraethyl orthosilicate, the reinforcing phase is nano-silicon carbide particles, the modified binder is epoxy resin modified with silane coupling agent KH-560, and the dispersant is octadecanoic acid.
3. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The preparation steps of the modified foaming agent are as follows: Take titanium hydride powder with a particle size of 10-20 μm, disperse it in a 3:1 volume ratio ethanol-water mixed solution, and sonicate for 30 min to form a suspension; add 5-8% of tetraethyl orthosilicate by mass of titanium hydride, add dilute ammonia dropwise to adjust the pH to 8-9, stir at 30℃ for 2 h, so that tetraethyl orthosilicate hydrolyzes on the surface of titanium hydride to generate silica sol; after filtration, vacuum dry at 80℃ for 4 h to obtain silica-coated titanium hydride, and obtain the modified foaming agent.
4. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The modified adhesive is prepared by placing epoxy resin in a three-necked flask, heating it to 60-70°C in a water bath with a stirring speed of 300-500 r / min, slowly adding silane coupling agent KH-560 at 3-5% of the epoxy resin mass, and stirring at a stirring speed of 300-500 r / min for 1-1.5 h. After cooling to room temperature, the modified epoxy resin is obtained, and the modified adhesive is obtained.
5. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The gradient aluminum foam matrix is composed of the following raw materials in parts by weight: 100 parts aluminum powder, 1-3 parts modified foaming agent, 5-8 parts reinforcing phase, 5-10 parts modified binder, and 0.5-1 parts dispersant.
6. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The preparation steps of the gradient aluminum foam matrix are as follows: Step 1: Weigh aluminum powder, modified foaming agent, reinforcing phase, and dispersant according to the mass ratio, add them to a mixer, and mix at 300-500 r / min for 20-30 min under inert gas protection to obtain premixed powder; Step 2: Add the modified binder to the premixed powder and continue mixing at 200-300 r / min for 15-20 min to obtain the molding powder. Step 3: Load the molding powder into the mold and cold press it under a pressure of 15-20MPa for 5-10 minutes to obtain the green body; Step 4: Place the green billet into a sintering furnace, first heat it to 450℃ at 5℃ / min and hold it for 0.5h; then heat it to 620-650℃ at 3℃ / min and hold it for 2-3h for foaming and sintering; finally cool it to room temperature with the furnace to obtain a gradient aluminum foam matrix.
7. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that: The complexing agent is sodium citrate, the buffer is sodium acetate, and the stabilizer is thiourea.
8. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The modified reducing agent is... The compound of doped sodium hypophosphite and hydrazine hydrate in a mass ratio of (3-5):1 is added directly to the plating solution during use.
9. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The preparation steps of the surface conductive layer are as follows: Step 1, Matrix pretreatment: Immerse the gradient aluminum foam matrix in sodium hydroxide solution for degreasing, then immerse it in nitric acid solution for acid washing and activation, pre-immerse it in an aqueous solution containing 2% complexing agent, soak it at 30℃ for 3 minutes, rinse it with deionized water and drain it. Step 2, Plating solution preparation: The chemical plating solution is composed of the following raw materials in parts by weight: 100 parts nickel sulfate, 8-12 parts modified reducing agent, 5-10 parts complexing agent, 3-6 parts buffer, and 1-2 parts stabilizer. First, dissolve the nickel sulfate, complexing agent, and buffer in deionized water and stir until completely dissolved. Then adjust the pH to 4.5-5.
5. Next, add the modified reducing agent and stabilizer, stir evenly, and heat to 50-55℃ to obtain the chemical plating solution. Step 3, chemical plating: Suspend the pretreated gradient aluminum foam substrate in the chemical plating solution, maintain the solution temperature at 50-55℃ and the stirring speed at 200r / min, and plating for 30-40min; Step 4, Post-treatment: Take out the plated substrate, rinse it three times with 60℃ deionized water, and dry it in an 80℃ forced-air drying oven for 20 minutes; then put it into a vacuum furnace and heat it to 150℃, keep it at that temperature for 1 hour, and then cool it to room temperature with the furnace to complete the preparation of the surface conductive layer.
10. The lightweight foamed aluminum-based integrated structural component for electronic device chassis according to claim 1, characterized in that, The fabrication steps of the biomimetic ventilation channel are as follows: Step 1, Preliminary processing: The gradient aluminum foam matrix is pre-formed using CNC milling technology. The milling speed is 8000-10000 r / min, the feed rate is 500-800 mm / min, and the channel cross-section is rectangular with a width of 5-10 mm and a height of 3-5 mm. Step 2, Cut-off waveguide structure processing: On the inner wall of the channel after preliminary processing, the cut-off waveguide structure is processed by laser engraving. The side length of the cross section of the waveguide structure is 2-5mm, and the spacing between adjacent waveguides is 3-6mm. Step 3, Micron-level fin processing: Micron-level fins are processed on the surface of the waveguide structure using electrolytic etching. The fin height is 0.5-1mm, the fin spacing is 1-2mm, the etching current density is 10-15A / dm², and the etching time is 10-15min to obtain a biomimetic ventilation channel.
